New Insights Into Functions of IQ67-Domain Proteins - Guo, Chunyue; Zhou, Jun; Li, Dengwen (Frontiers in Plant Science, 2021)
IQ67-domain (IQD) proteins, first identified in Arabidopsis and rice, are plant-specific calmodulin-binding proteins containing highly conserved motifs. They play a critical role in plant defenses, organ development and shape, and drought tolerance. Driven by comprehensive genome identification and analysis efforts, IQDs have now been characterized in several species and have been shown to act as microtubule-associated proteins, participating in microtubule-related signaling pathways. However, the precise molecular mechanisms underpinning their biological functions remain incompletely understood. Here we review current knowledge on how IQD family members are thought to regulate plant growth and development by affecting microtubule dynamics or participating in microtubule-related signaling pathways in different plant species and propose some new insights.